What Vowels Can Tell Us about the Evolution of Music - Fenk-Oczlon, Gertraud (Frontiers in Psychology, 2017)
Whether music and language evolved independently of each other or whether both evolved from a common precursor remains a hotly debated topic. We here emphasize the role of vowels in the language-music relationship, arguing for a shared heritage of music and speech. Vowels play a decisive role in generating the sound or sonority of syllables, the main vehicles for transporting prosodic information in speech and singing. Timbre is, beyond question, the primary parameter that allows us to discriminate between different vowels, but vowels also have intrinsic pitch, intensity, and duration. There are striking correspondences between the number of vowels and the number of pitches in musical scales across cultures: a maximum of roughly 12 elements, a minimum of 2, a frequency peak at 5 to 7 elements, and the pentatonic scale and the 5-vowel systems as the most common. Moreover, we reveal coincidences between vowels and scales even in specific geographical regions and cultures. For example, languages with up to 4 vowels (e.g. Navaho, Cheyenne) tend to have tritonic or tetratonic scales, and languages with more than 5 vowels (e.g., Hopi) hexatonic or heptatonic scales. We will discuss the co-variation between vowel inventories and musical scales in the context of other ethnomusicological findings and with respect to singing and half-musical communication, both in ontogeny and phylogeny.